Shades of gray: Conscientious objection in medical assistance in dying. Issue 1 (4th July 2019) - Pesut, Barbara; Thorne, Sally; Greig, Madeleine
Abstract: With the advent of legalized medical assistance in dying [MAiD] in Canada in 2016, nursing is facing intriguing new ethical and theoretical challenges. Among them is the concept of conscientious objection, which was built into the legislation as a safeguard to protect the rights of healthcare workers who feel they cannot participate in something that feels morally or ethically wrong. In this paper, we consider the ethical complexity that characterizes nurses' participation in MAiD and propose strategies to support nurses' moral reflection and imagination as they seek to make sense of their decision to participate or not. Deconstructing the multiple and sometimes conflicting ethical and professional obligations inherent in nursing in such a context, we consider ways in which nurses can sustain their role as critically reflective moral agents within a context of a relational practice, serving the diverse needs of patients, families, and communities, as Canadian society continues to evolve within this new way of engaging with matters of living and dying.